Albuminuria Is Associated with Left Ventricular Hypertrophy in Patients with Early Diabetic Kidney Disease - Nan Wu; Weiwei Zhao; Kuanping Ye; Yintao Li; Min He; Bin Lu; Renming Hu (International Journal of Endocrinology)
Aims. Left ventricular hypertrophy (LVH) and albuminuria are both markers for cardiovascular diseases (CVDs) in patients with type 2 diabetes mellitus (T2DM). We speculate that albuminuria in T2DM patients with early diabetic kidney disease (DKD) could predict LVH. Methods. 333 diabetic patients (219 non-DKD and 114 early DKD) were enrolled. The association between albuminuria and LVMI was examined using multivariate linear regression and logistic regression. Results. The rate of LVH was significantly higher in patients with early DKD versus those without DKD (57.0% versus 32.9%; P<0.001). Multivariate linear regression analysis demonstrated that albuminuria status (no, micro-, and macroalbuminuria; P<0.001), age (P<0.001), systolic blood pressure (P=0.0578), and the use of ACEI/ARB drug (P<0.001) were independently associated with LVMI. The risks were substantially higher for LVH in the microalbuminuria group (odds ratio 2.473 (95% confidence interval 1.370–4.464)) and macroalbuminuria group (odds ratio 3.940 (95% confidence interval 1.553–9.993)) compared with that in non-DKD group. Concentric hypertrophy was the most common geometric pattern in patients with early DKD (36.0%), followed by eccentric hypertrophy (21.0%). Conclusions. Albuminuria is associated with higher LVMI and higher rate of LVH in patients with early phase DKD.